Perencanaan Sistem Jaringan Mikro (Microgrid) Dengan Supply dari Pembangkit Listrik Tenaga Surya (PLTS) dan Generator Set di Jurusan Teknik Elektro Universitas Udayana - Putra, I. P. Krisna Darma; Giriantari, I. A. Dwi; Wijaya, I W. Arta (Jurnal Teknologi Elektro, 2015)
Network design Micro Electrical Engineering  Department of the University of Udayana aims to harness solar power contained in the Department of Electrical Engineering are still stand alone system, namely, its use is still limited area of internet corner, has not been used as one of the suppliers of electrical power for the building - a building in the Department of Electrical Engineering. Based on simulation results show PLTS only able to serve load in an on-grid of 0.66% of the total production of electrical energy generated while the condition of the off-grid solar power can only serve load building DJs and building DH (load lighting and socket) at 3:21% and generator sets were installed in the Department of Electrical Engineering serve at 96.79%. Solar power capacity to be installed to meet the entire load of the building in the Department of Electrical Engineering is equal to the number of 211.814 Watt PV Module is needed as much as 26.267 pieces. This amount is influenced by the size of the capacity and efficiency of PV Module installed at this time.
Keywords: Microgrid, PV Module, PLTS, generator set, on- grid, off-grid